Cross‐sectional and longitudinal associations between psychosocial well‐being and sleep in European children and adolescents. (4th January 2019) - Thumann, Barbara F.; Börnhorst, Claudia; Michels, Nathalie; Veidebaum, Toomas; Solea, Antonia; Reisch, Lucia; Moreno, Luis A.; Lauria, Fabio; Kaprio, Jaakko; Hunsberger, Monica; Felső, Regina; Gwozdz, Wencke; et al.
Abstract: Research on associations of positive mental health, in contrast to mental ill‐health, with sleep duration and sleep disturbances in young populations is scarce. In particular, longitudinal studies focussing on the influence of positive mental health on sleep characteristics are lacking. Therefore, we investigated cross‐sectional and longitudinal associations of psychosocial well‐being with sleep duration and sleep disturbances. For the cross‐sectional analysis, we used data of 3‐15‐year‐old children and adolescents participating in the 2013/14 examination of the European IDEFICS/I.Family cohort study ( N = 6, 336). The longitudinal analysis was restricted to children who also participated in the 2009/10 examination ( N = 3, 379). Associations between a psychosocial well‐being score created from 16 items of the KINDL R Health‐Related Quality of Life Questionnaire covering emotional well‐being, self‐esteem and social relationships, an age‐standardized nocturnal sleep duration z ‐score and two sleep disturbance indicators ("trouble getting up in the morning", "difficulties falling asleep") were estimated using linear and logistic mixed‐effects models. Cross‐sectionally, a higher well‐being score was associated with longer sleep duration and lower odds of sleep disturbances. A positive change in the well‐being score over the 4‐year period was associated with longer sleep duration and lower odds of sleep disturbances at follow‐up. However, there was only weak evidence that higher psychosocial well‐being at baseline was associated with better sleep 4 years later. Thus, our results suggest that increases in well‐being are associated with improvements in both sleep duration and sleep disturbances, but that well‐being measured at one point in time does not predict sleep characteristics several years later.